2021
DOI: 10.1111/bjh.17537
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported fatigue refines prognosis in higher‐risk myelodysplastic syndromes (MDS): a MDS‐CAN study

Abstract: The incorporation of patient-reported outcomes with traditional disease risk classification was found to strengthen survival prediction in patients with myelodysplastic syndromes (MDS). In the present Canadian MDS registry analysis, we validate a recently reported prognostic model, the Fatigue-International Prognostic Scoring System among higher-risk patients [FA-IPSS(h)], which incorporates patients' reported fatigue, assessed by the European Organization for Research and Treatment of Cancer (EORTC) Quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…This finding has been replicated across several cancer populations with both solid and haematological malignancies, 27,28 and patient-reported outcome data have also been successfully integrated into established diseaserisk classifications to improve their accuracy in predicting survival. 29,30 Therefore, an important question to be elucidated in further analyses is whether our baseline patient-reported outcome data could provide independent prognostic information for survival outcomes. Such evidence would lay the groundwork for the development of a patient-centric relapsed or refractory multiple myeloma frailty index, by integrating (or even replacing) individual components of the IMWG frailty score algorithm with patient-reported outcome information.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has been replicated across several cancer populations with both solid and haematological malignancies, 27,28 and patient-reported outcome data have also been successfully integrated into established diseaserisk classifications to improve their accuracy in predicting survival. 29,30 Therefore, an important question to be elucidated in further analyses is whether our baseline patient-reported outcome data could provide independent prognostic information for survival outcomes. Such evidence would lay the groundwork for the development of a patient-centric relapsed or refractory multiple myeloma frailty index, by integrating (or even replacing) individual components of the IMWG frailty score algorithm with patient-reported outcome information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Palmer et al found that changes in PROs predicted survival in patients with chronic GVHD [13]. Some studies have also shown that inclusion of PROs (i.e., fatigue) in well-established risk score classifications may improve their prognostic accuracy, as was the case for patients with myelodysplastic syndromes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“… 13 Fatigue, as reported by patients themselves, has also been successfully incorporated into well‐established disease risk classifications to enhance their prognostic accuracy in higher‐risk MDS patients. 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…13 Fatigue, as reported by patients themselves, has also been successfully incorporated into well-established disease risk classifications to enhance their prognostic accuracy in higher-risk MDS patients. [14][15][16] To date, HRQoL in MDS research has been frequently assessed with non-MDS-specific measures, 17 possibly limiting our understanding of the full breadth of problems experienced by these patients. Disease-specific measures are more likely to capture key elements of HRQoL most relevant to the population being studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation